Letter to candidates for California State Legislative Offices from Ralph Flynn, Executive Director, California Teachers Association - Ralph Flynn:::::: (1976)
In an April 6, 1976 letter, the California Teachers Association invited candidates for state legislative offices to attend an orientation session on public school finance and legislation. The sessions were scheduled for April 20 in Burlingame and April 22 in Los Angeles. CTA/NEA planned to provide in-depth analysis and discussion on issues such as school finance and collective bargaining, the Serrano-Priest decision, legislative proposals, financially distressed school districts, and needed educational reforms. The briefings would include experienced speakers, opportunities for dialogue, media participation, and access to finance data and materials. Candidates were asked to RSVP by returning a form or contacting CTA representatives in Burlingame or Los Angeles.